Community based nutrition education intervention to improve nutritional status and feeding practice of children in Mahottari district of Nepal. - Yadav, Dipendra Kumar (2015)
ABSTRACT: Maternal and child mortality have declined significantly in Nepal to the extent that Nepal is on track to meet the millennium development goals for maternal and child mortality. Similar improvements have not been seen in general nutrition status of them (Codling 2011). In India, research conducted on community-based nutrition education for improving infant growth in rural Karnataka reported that nutrition education and counseling were significantly associated with increased weight velocity among girls and improved feeding behaviour among both boys and girls (Kilaru, Griffiths et al. 2005). Objectives of the study were to assess the nutritional status of children, to identify the correlations between social-demographic characteristics and nutritional status of children and to find the effect of nutrition-education intervention on nutritional status and feeding practices of children. Study design was an intervention with pre-post control design. Two groups of village development committees (VDCs) from Mahottari district were recruited as interventional and control areas. The intervention was for 12-month nutrition education program and comprised of twelve 2-3 hour nutrition lectures and discussion classes conducted by the female community health volunteers (FCHVs). Study shows that stunting increased by 1.3 per cent in control group while marginally (0.1%) increased in intervention group from baseline to end-line period. Number of underweight children increased by 7.6 per cent in control group while it decreased by 17.7% in intervention group from baseline to end-line. Wasting increased by 11.4 per cent in control group where as it decreased by 5.6 per cent in intervention group from baseline to end-line. Nutrition education intervention was effective to reduce wasting and underweight but did not helped to reduce the stunting status of children. Stunting reflects failure to receive adequate nutrition over a long period of time and is affected by recurrent and chronic illness. Findings suggested that longer duration of nutritional intervention programmes should be implemented to control the stunting status of children. Keywords: Nutrition education, Stunting, Wasting, Underweight